Rare variants in MYD88, IRAK4 and IKBKG and susceptibility to invasive pneumococcal disease : a population-based case-control study - Ellis, M; Elliott, K; Rautanen, A; Crook, D; Hill, A; Chapman, S (Public Library of Science, 2015)
Although rare variants within the Toll-like receptor signalling pathway genes have been found to underlie human primary immunodeficiencies associated with selective predisposition to invasive pneumococcal disease (IPD), the contribution of variants in these genes to IPD susceptibility at the population level remains unknown. Complete re-sequencing of IRAK4, MYD88 and IKBKG genes was undertaken in 164 IPD cases from the UK and 164 geographically-matched population-based controls. 233 single-nucleotide variants (SNVs) were identified, of which ten were in coding regions. Four rare coding variants were predicted to be deleterious, two variants in MYD88 and two in IRAK4. The predicted deleterious variants in MYD88 were observed as two heterozygote cases but not seen in controls. Frequencies of predicted deleterious IRAK4 SNVs were the same in cases and controls. Our findings suggest that rare, functional variants in MYD88, IRAK4 or IKBKG do not significantly contribute to IPD susceptibility in adults at the population level.